Vialidad y diseño de un proyecto turístico hostal en Mindo, Provincia de Pichincha. - Abril Donoso, María Marcela (2004)
Mindo Parish has a high tourism potential by having several natural attractions, which record a broadcast at national and international level, the main attractions are: El Bosque Protector Mindo Nambillo Nambillo the Cascade River and Rio Mindo where extreme and adventure as boating, sailing boats and tubes with playing sports; He has also been regarded as an ecological paradise for the diversity of birds, butterflies and flowers unique in the world, so this area is visited by domestic and foreign tourists in all seasons. The development of market studies, technical and financial as well as social and ecological analysis for this project, determine their viability and great chance of success in the market. Hostal, "CABAÑAS Mindo" will be top-notch and will be located in the central area of ​​the parish of Mindo, northwest of the province of Pichincha, will have 12 rooms and a total capacity of 32 people. Accommodation services and catering services complemented provide recreation as grills, camping, barbecues, nature trails, over Canchupí river and game room; for the convenience of customers will have private parking, laundry and ironing services, hot water, telephone and utilities.